Probing cultural differences in product design and consumer evaluation using repertory grid analysis - Tang, Pinyan; Lawson, Glyn; Sun, Xu; Sharples, Sarah (2021)
Culture plays an essential role in the success of product design, especially in the age of a global economy where there is a high probability of discrepancy between the designer's intention and the consumer's response. However, the role of culture is often challenging to identify and measure. In the current paper, we employed Repertory Grids (RG) to investigate differences in UK and Chinese participants' evaluations of designs, which were themselves from both UK and Chinese students. The techniques of Honey's Content Analysis (HCA) and Principal Components Analysis (PCA) were applied to integrate the analysis of both the collected qualitative and quantitative data. The results show that the two groups tended to focus on a similar range of design aspects (i.e. aesthetics, form/shape, usability, creativity, and functionality), but apply different criteria in evaluating such aspects.The UK and Chinese designs were found to be distinctive from each other and tended to appeal more to the people from the same cultural background. The findings reveal the interplay between culture and design and underline the importance of integrating culture into design education.